Odpowiedzi

Najlepsza Odpowiedź!
2010-02-01T16:04:23+01:00
1. ( 2x - 1 ) + ( 4x - 2 ) + ( x + 1 ) = 2x - 1 + 4x -2 + x + 1 = 7x - 2
2. ( 4x - 2 ) + ( 2x + 1 ) + ( x - 1 ) = 4x - 2 + 2x + 1 + x - 1 + 7x - 2
3. ( x + 1 ) + ( 3x - 1 ) + ( 3x - 2 ) = x + 1 + 3x - 1 + 3x - 2 = 7x - 2
4. ( 2x - 1 ) + ( 2x - 2 ) + ( 3x + 1 ) = 2x - 1 + 2x - 2 + 3x + 1 = 7x - 2
5. ( 4x - 2 ) + ( 2x + 1 ) + ( x - 1 ) = 4x - 2 + 2x + 1 + x - 1 = 7x - 2
6. ( x + 1 ) + ( 3x - 1 ) + ( 3x - 2 ) = x + 1 + 3x - 1 + 3x - 2 = 7x - 2
7.( 2x - 1 ) + ( 2x + 1 ) + ( 3x - 2 ) = 2x - 1 + 2x + 1 + 3x - 2 = 7x - 2
8.( x + 1 ) + ( 2x + 1 ) + ( 3x + 1 ) = x + 1 + 2x + 1 + 3x + 1 = 6x + 3

Odpowiedź : To Nie Jest Kwadrat Magiczny . !
2 5 2